2016
DOI: 10.4187/respcare.04566
|View full text |Cite
|
Sign up to set email alerts
|

Should Early Mobilization Be Routine in Mechanically Ventilated Patients?

Abstract: ICU-acquired weakness is a major complication of critical illness requiring mechanical ventilation.Early mobilization has been shown to decrease the negative consequences of ICU-acquired weakness. However, early mobilization might entail risks to the patient. Additional staffing needs might have a negative financial impact. This review examines whether early mobilization should be routinely performed in mechanically ventilated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
0
10
0
8
Order By: Relevance
“…A recent systematic review of quantitative and qualitative studies identified weakness as an important capability-related barrier to mobilization 31 . The low prevalence of mobilization practice and of patients mobilized out of bed observed in our study, regardless of length of ICU stay and duration of MV, may be explained by the difficulty in mobilizing patients when they are in the critical phase of their disease and, subsequently, because they experience the effects of such immobility, creating a cycle of immobility 32 . Therefore, weakness should be a key reason why early mobilization is of great importance in the ICU.…”
Section: Discussionmentioning
confidence: 57%
“…A recent systematic review of quantitative and qualitative studies identified weakness as an important capability-related barrier to mobilization 31 . The low prevalence of mobilization practice and of patients mobilized out of bed observed in our study, regardless of length of ICU stay and duration of MV, may be explained by the difficulty in mobilizing patients when they are in the critical phase of their disease and, subsequently, because they experience the effects of such immobility, creating a cycle of immobility 32 . Therefore, weakness should be a key reason why early mobilization is of great importance in the ICU.…”
Section: Discussionmentioning
confidence: 57%
“…Despite good results in some studies, safety concerns remain a key element for mobilizing patients while receiving mechanical ventilation. 3 Early mobilization does not just mean walking. Other tools used to actively mobilize patients include in-bed cycling, dangling from the bed, standing, and bedside transfers from bed to a chair.…”
Section: Enhancing Early Mobility With a Speaking Valvementioning
confidence: 99%
“…In the absence of early mobilization, patients are further prone to ICU-acquired weakness and functional disability. 3 Fatigue, weakness, and decreased functional status are known to last up to 1 year in ICU survivors. Early mobility is associated with decreased ICU length of stay, decreased hospital length of stay, decreased hospital readmissions, and, importantly, increased ventilator-free days.…”
Section: Enhancing Early Mobility With a Speaking Valvementioning
confidence: 99%
“…30% of stroke survivors are estimated to develop some level of dependence that prevents them to perform basic daily activities [6]. Treatment at Intensive Care Units (ICU) and the period after a critical medical episode are also associated with increased physical and psychological morbidity [7]. When we focus on the patient functional rehabilitation, after patients, hemodynamic and respiratory stabilization, early rehabilitation has been seen as a positive intervention that works as an important treatment and modifies the probability of developing negative effects related to functional and physical morbidity.…”
Section: Introductionmentioning
confidence: 99%